Toward Better Management of Flood Losses: Flood Insurance in a Wetter World. (January 2019) - McShane, Michael K.; Yusuf, Juita-Elena (Wie)
Flood is the most frequent and costly of U.S. natural disasters with losses expected to increase due to climate change. The National Flood Insurance Program (NFIP) mandates flood insurance purchase for properties with federally backed mortgages in the 100-year floodplain. We propose that mandatory flood insurance purchase be extended to all property in the 500-year floodplain. Following flood events, payments would be directly provided for more properties that suffer flood loss, reducing federal disaster aid spending. The mandate could put more pressure on local governments to increase their Community Rating System score, such as through infrastructure investments and management practices that reduce flood risk. The expanded requirement would not address the inaccuracies of maps used to price flood insurance (and used by local governments to make long-term planning decisions) but may affect floodplain development by making more explicit the costs and risks of building and living in high-risk areas.